The Death-Nanny Give Relief. About Images of Death in Literary period Young Poland in the Selected Poems of Bronisława Ostrowska and Maryla Wolska - Jankowska, Aldona (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
My concept of the article was to present the death in literary period Young Poland. The article basisof selected poems of Bronisława Ostrowska and Maryla Wolska.The death and love were in Young Poland movement main literary subjects. In literary period YoungPoland differently a death was understood — as the beautiful, gentle women —Madame Mors — thereverse of Danse macabre. The death–nanny give relief and calm.This motive and kind of the death was very popular in Young Poland literary period.